Materialne przesłanki przeszukania w k.p.k. - Pikul, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article raises the issue of determining and interpreting material grounds for search. The author points out the problems that might hinder the police or other law enforcement authorities in performing the search under investigative procedures.
Keywords: procedury dochodzeniowe; przeszukania; policja; podejrzany